The role of prescribed fire in the provision of regulating ecosystem services of Spanish heathlands - Calvo, Leonor; Huerta, Sara; Marcos, Elena; Calvo-Fernández, Javier; Taboada, Angela (Ecological Questions, 2015)
We provide a synthesis of evidence of the effects of burning and N deposition on the provision of regulating ecosystem services of Cantabrian heathlands (NW Spain). We quantified carbon sequestration in litter, above and belowground biomass, root and soil compartments in heathlands after burning and burning plus N fertilization.